The role of urban green space for human well-being - Christine Bertram; Katrin Rehdanz (Kiel Institute for the World Economy (IfW), 2014)
Most people in Europe live in urban environments. For these people, urban green space is an important element of well-being, but it is often in short supply. We use self-reported information on life satisfaction and different individual green space measures to explore how urban green space affects the well-being of the residents of Berlin, the capital city of Germany. We combine spatially explicit survey data with spatially highly disaggregated GIS data on urban green spaces. We observe a significant, inverted U-shaped effect of the amount of and distance to urban green space on life satisfaction. According to our results, the optimal amount of green space in a 1 km buffer is 36 ha, or 11.5% of the buffer area, and 75% of the respondents have less green space available. Our results are robust to a number of robustness checks.
Keywords: I31; Q51; Q57; R00; 330; life satisfaction; urban ecosystem services; urban green space; well-being